2022
DOI: 10.1111/lam.13661
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and physicochemical properties of Ocimum essential oil loaded in poly(lactic acid) nanofibers

Abstract: Significance and Impact of the Study: The continuous and improper application of synthetic fungicides can favour the selection of resistant OTA-producing fungi, and it can result in the induction of the biosynthesis of this toxic substance. In addition, it can cause adverse health effects for consumers. Essential oils are chemically safe and acceptable to consumers. The essential oils from Ocimum basilicum and Ocimum gratissimum encapsulated in lactic polyacid nanofibres hold promise for the control of fungal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Brandão et al (2022) studied the essential oil from O. basilicum and observed that the principal constituents were linalool (26.89%), 1,8‐cineole (23.62%), and camphor (15.69%). At the same time, Alimi et al (2022) reported that trazole (80.87%) and linalool (16.12%) were the main constituents of the essential oil from O. basilicum , with a yield of 0.24%.…”
Section: Resultsmentioning
confidence: 99%
“…Brandão et al (2022) studied the essential oil from O. basilicum and observed that the principal constituents were linalool (26.89%), 1,8‐cineole (23.62%), and camphor (15.69%). At the same time, Alimi et al (2022) reported that trazole (80.87%) and linalool (16.12%) were the main constituents of the essential oil from O. basilicum , with a yield of 0.24%.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the materials also showed efficacy against S. aureus and P. aeruginosa bacteria strains. Recently, EOs from Ocinum basilicum and Ocinum gratissinum were successfully encapsulated into PLA nanofibers by blow spinning method [ 87 ]. By mixing different proportions of the mentioned EOs, it allowed the bioactive materials to display effectiveness as an antifungal against Aspergillus ochraceus and Aspergillus westerdjikiae .…”
Section: Antimicrobial Electrospun Nanofibrous Matsmentioning
confidence: 99%